Analysis of Patients’ Characteristics and Treatment Profile of People Who Use Drugs (PWUDs) with and without a Co-Diagnosis of Viral Hepatitis C: A Real-World Retrospective Italian Analysis - Nava FA; Mangia A; Riglietta M; Somaini L; Foschi FG; Claar E; Maida I; Ucciferri C; Frigerio F; Hernandez C; Dovizio M; Perrone V; et al. (Dove Medical Press, 2023)
Felice Alfonso Nava,1 Alessandra Mangia,2 Marco Riglietta,3 Lorenzo Somaini,4 Francesco Giuseppe Foschi,5 Ernesto Claar,6 Ivana Maida,7 Claudio Ucciferri,8 Francesca Frigerio,9 Candido Hernandez,10 Melania Dovizio,11 Valentina Perrone,11 Luca Degli Esposti,11 Massimo Puoti12 1U.O. Sanità Penitenziaria e Area Dipendenze, Azienda ULSS 6 Euganea, Padova, Italy; 2UOS Epatologia, Istituto di Ricovero e Cura "Casa Sollievo della Sofferenza", S. Giovanni Rotondo, Italy; 3UOC Dipendenze, ASST Papa Giovanni XXIII, Bergamo, Italy; 4Servizio per le Dipendenze, SERT di Cossato, Biella, Italy; 5UOC Medicina Interna, Ospedale di Faenza, Faenza, Italy; 6UOC Medicina Interna, Ospedale Evangelico "Villa Betania", Napoli, Italy; 7UOC Malattie Infettive e Parassitarie, Azienda Ospedaliero Universitaria di Sassari, Sassari, Italy; 8Clinica di Malattie Infettive Ospedale "SS Annunziata", Chieti, Italy; 9Gilead Sciences, Milano, Italy; 10Gilead Sciences, Global Medical Affairs, Stockley Park, London, UB11 1BD, UK; 11CliCon S.R.L. Società Benefit, Health Economics and Outcomes Research, Bologna, Italy; 12SC Malattie Infettive, ASST Grande Ospedale Metropolitano Niguarda, Milano, ItalyCorrespondence: Luca Degli Esposti, CliCon S.r.l. Società Benefit, Health, Economics & Outcomes Research, Via Murri, 9, Bologna, 40137, Italy, Tel +39 544 38393, Fax +39 544 212699, Email luca.degliesposti@clicon.itPurpose: Hepatitis C virus (HCV) spreads from contact with blood of an infected person. HCV infections are common among people who use drugs (PWUDs), when sharing needles, syringes, or other equipment for injected drugs. The advent of pangenotypic direct-antiviral agents (DAA) in 2017 transformed the treatment landscape for HCV, but PWUDs remain a complex and hard-to-treat population with high risk of HCV reinfection. The aim of this real-world analysis was to characterize the demographic and clinical features of PWUDs in Italy, also focusing on comorbidity profile, treatment with DAAs, resource consumptions for the National Health System (NHS).Patients and Methods: During 01/2011- 06/2020, administrative databases of Italian healthcare entities, covering 3,900,000 individuals, were browsed to identify PWUDs with or without HCV infection. Among HCV+ patients, a further stratification was made into treated and untreated with DAAs. The date of PWUD or HCV first diagnosis or DAA first prescription was considered as index-date. Patients were then followed-up for one year. Alcohol-dependency was also investigated.Results: Total 3690 PWUDs were included, of whom 1141 (30.9%) PWUD-HCV+ and 2549 (69.1%) PWUD-HCV-. HCV-positive were significantly older (43.6 vs 38.5 years, p < 0.001), had a worse comorbidity profile (Charlson-index: 0.8 vs 0.4, p < 0.001), and high rates of psychiatric, respiratory, dermatological, musculoskeletal diseases and genitourinary (sexually transmitted) infections. Moreover, they received more drug prescriptions (other than DAAs, like anti-acids, antiepileptics, psycholeptics) and had undergone more frequent hospitalization, predominantly for hepatobiliary, respiratory system and mental disorders. DDA-untreated had significantly higher Charlson-index than DAA-treated (0.9 vs 0.6, p = 0.003). Alcoholism was found in 436 (11.8%) cases.Conclusion: This Italian real-world analysis suggests that PWUDs with HCV infection, especially those untreated with DAAs, show an elevated drug consumption due to their complex clinical profile. These findings could help to ameliorate the healthcare interventions on PWUDs with HCV infection.Keywords: drug abuse, hepatitis C virus, alcohol dependency, real-world evidence